Vocabulary Error Analysis in EFL Writing of Junior High School Students - Dian Pratiwi; Anisa Salsabila (EXPOSE (Journal of English Education and for Specific Purpose), 2024)
Vocabulary mastery is a fundamental aspect of writing in English as a foreign language, as it enables learners to express ideas accurately and meaningfully. Limited vocabulary often leads to errors that reduce the clarity and quality of students written texts. This study aims to analyze the types of vocabulary errors in junior high school students English writing and identify the factors contributing to these errors. A descriptive qualitative approach with document analysis was employed, analyzing 20 written texts from students of SMP Negeri 4 Pringsewu. The findings reveal that vocabulary errors are prevalent and systematic, with word choice errors and lexical error chains being the most dominant. Other common errors include word form, collocation, and semantic errors, often caused by interlanguage development, limited depth of vocabulary knowledge, cognitive load, and insufficient integration of vocabulary instruction with writing practice. The study concludes that vocabulary errors in EFL writing are interconnected rather than isolated and significantly affect writing quality. For educational practice, it is recommended that teachers integrate contextualized vocabulary instruction into writing activities, emphasize collocations and semantic accuracy, and use writing tasks as diagnostic tools to improve students lexical competence.